Memorias y escrituras de la Resistencia en Italo Calvino (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
This article aims to explore the representations of the anti-fascist resistance of the partisans in Italo Calvino’s work, focusing on its testimonial and memorialistic form, its transpositions through autobiographical lyricism, the “pathos of distance”, its political and moral interpellations, and its semantic and stylistic constants. The corpus comprises the novel Il sentiero dei nidi di ragno, the partisan tales in Ultimo viene il corvo, the story “Flirt prima di battersi”, and a selection of articles. The aim is to reconstruct the complex process of discursivizing Calvino’s political and military experience, a process that brought together a generation of writers committed to antifascist ideals and spurred the moral and cultural reconstruction of Italy.
Keywords: Antifascism; Resistance; Partisans; narrative; essay